THE PROCEDURE OF FORMING INDUSTRIAL ENTERPRISE INTEGRAL RISK MANAGEMENT PROGRAMS - V. A. Konovalov (Модернизация, инновация, развитие, 2016)
The issue of forming integral risk management programs is vital for industrial enterprises. A new option of solving the task is discussed. Industrial enterprise risk management general structure is proposed for the whole integrity of risks, detailed description of the procedure of forming thisprogram being provided for. Subprograms of the management of current and positioned risks as well as of enterprise project risks are described in the article along with the succession of operations needed.